Projeto de minigeração distribuída solar fotovoltaica de 3 mw para o Campus do Pici da Universidade Federal do Ceará - Silva, Karlos Daniel Menezes e (2016)
This work presents the design of a distributed solar photovoltaic minigeneration plant with installed capacity of 3 MW to be connected to the medium voltage internal network of the Pici Campus of the Federal University of Ceara and to feed part of its loads in order to considerably reduce its costs with electricity. In Brazil, distributed generation was regulated by Normative Resolution No. 482/2012 of ANEEL, which also created the Electric Energy Compensation System. In 2015, this resolution was updated by Normative Resolution No. 687/2015, which brought even more advantages to all those who wanted to produce their own electricity. In the design of the photovoltaic generator (direct current side of the plant), the maximum and minimum historical temperatures of the installation site of the plant are taken into account, since the temperature directly influences the voltages of the photovoltaic generator. Thus, it must be ensured that, for all possible temperature conditions, the voltages of the photovoltaic generator remain within the limits allowed by the inverter. The photovoltaic generator consists of 11,340 photovoltaic modules of 315 Wp, resulting in a nominal power of 3,572.10 kWp. The installed capacity of the plant is given by three inverters of 997.70 kVA, each connected to 3,780 modules configured in 180 series in parallel, each series with 21 modules. All conductors are dimensioned, both on the DC side and on the AC side, as well as the electrical protections, power transformers, switchgears and other elements required for connection to the medium voltage network. Based on daily average solar radiation data for Fortaleza/CE, it is estimated that the 3MW photovoltaic power plant will generate approximately 5,732 MWh per year. As a result, an economy of approximately 2.3 million reais per year with electricity can be achieved.